KONFLIK DAN PENGHULU; Pendekatan Mediasi Dalam Menyelesaikan Konflik Internal Kaum Oleh Penghulu Di Minangkabau - Muhammad Jamil (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The function of the Penghulu in Minangkabau is to maintain and prosper his people. Conflict is an obstacle to achieving the welfare goal. The headman as the leader of the Tribe has its own mechanism for managing conflict. This is driven by the values of locality to alleviate existing conflicts. Form of maintenance that strives for various conflicts that occur can be resolved by means of deliberation or commonly referred to as mediation. This article explains that in outline, the conflict is interpreted by the Minangkabau people with kusuik (tangled). Kusuik is classified according to the conditions of the individuals involved in the conflict, such as; Kusuik rambuik, Kusuik quill, kusuik banang, and kusuik tampuo nest. This conflict classification at the same time illustrates the conflict resolution that must be taken by the head to resolve it. The mechanism for the settlement was found; (1) Bulek aie ka pambuluah, bulek kato ka mufakat, (2) Koknyo singkek jan diuleh, ketek jan are stirred, bajalan luruih, bakato bana, (3) sadanciangbak stale, saciok like chicken, talungkuik eat the ground, talantang samo eat the wind; , good luck, katako, cilako, (4) nan ka finished, nan ka gadang, nan became a thorn in the dagiang, (5) sat seo ba samo ba roomy, sat down in the middle of the Sampik ba. The data was obtained through analysis of observations, interviews, and literacy based on case studies in Nagari Tabek Patah Kec. Salimpaung Tanah Datar Regency